Marginal accuracy of nickel chromium copings fabricated by conventional and accelerated casting procedures, produced with ringless and metal ring investment procedures: A comparative in vitro study - Deepa Alex; Y Bharath Shetty; Glynis Anita Miranda; M Bharath Prabhu; Reshma Karkera (Wolters Kluwer Medknow Publications, 2015)
Background: Conventional investing and casting techniques are time-consuming and usually requires 2-4 h for completion. Accelerated nonstandard, casting techniques have been reported to achieve similar quality results in significantly less time, namely, in 30-40 min. During casting, it is essential to achieve compensation for the shrinkage of solidifying alloy by investment expansion. The metal casting ring restricts the thermal expansion of investment because the thermal expansion of the ring is lesser than that of the investment. The use of casting ring was challenged with the introduction of the ringless technique. Materials and Methods: A total of 40 test samples of nickel chromium (Ni-Cr) cast copings were obtained from the patterns fabricated using inlay casting wax. The 20 wax patterns were invested using metal ring and 20 wax patterns were invested using the ringless investment system. Of both the groups, 10 samples underwent conventional casting, and the other 10 underwent accelerated casting. The patterns were casted using the induction casting technique. All the test samples of cast copings were evaluated for vertical marginal gaps at four points on the die employing a stereo optical microscope. Results: The vertical marginal discrepancy data obtained were tabulated. Mean and standard deviations were obtained. Vertical discrepancies were analyzed using analysis of variance and Tukey honestly significantly different. The data obtained were found to be very highly significant (P < 0.001). Mean vertical gap was the maximum for Group II (53.64 μm) followed by Group IV (47.62 μm), Group I (44.83 μm) and Group III (35.35 μm). Conclusion: The Ni-Cr cast copings fabricated with the conventional casting using ringless investment system showed significantly better marginal fit than that of cast copings fabricated from conventional and accelerated casting with metal ring investment and accelerated casting using ringless investment since those copings had shown the least vertical marginal discrepancies among the four methods evaluated in this study.